THE INFLUENCE OF NIAL PARTICLE SIZE ON IMPACT RESISTANCE AND WEAR RESISTANCE OF THERMAL SPRAYED CR3C2-NIAL-AL2O3 COATING - HADY RASFA (NIM : 13706050); Pembimbing : Dr. Husaini Ardy Dr. Eng. Budi Prawara, ASYRAFUL
High velocity oxygen fuel ( HVOF) thermal spray coating is one of the surface treatment processes to obtain wear resistant coating. One of the factors that determine coating characteristic is feedstock powder, such as powder type, powder composition, powder morphology and size. The alloy of carbide and metal powders or intermetallic was applied to obtain coating with high wear and impact resistances. Feedstock powder of Cr3C2-NiAl-Al2O3 with weight ratio of 60 : 30 : 10 was deposited by high velocity oxygen fuel (HVOF) process onto the surface of low carbon steel substrate. The objective of this study is to examine the effect of NiAl particle size, that is - 125 μm (-120 mesh), -75 μm (-200 mesh), -53 μm (-270 mesh), - 38 μm (-400 mesh) in feedstock powder to sliding wear and impact resistances of the coating layer. The effect of surface roughness ( Ra and Ry) and hardness of coating on the wear resistance are examined by pin on disc sliding wear test. The impact resistance of coating will be examined by repeated impact test, where the number of impact cycle for coating failure will be observed. The result obtained showed that by decreasing the NiAl particle size; the hardness of coating increases, the surface roughness of coating decreases. The weight loss of coating decreases, and the number of impacts to failure increases. However, it was found that the impact cycle to failure of -38 μm NiAl particle size is much less than that of -53μm. Further examinations by optical micrograph revealed that failure of -38 μm NiAl occurred by intercoating layer failure; while failure of -53 μm NiAl occurred by substrate/coating interfacial failure.